Body centered cubic carbon BC14: An all-sp(3) bonded full-fledged pentadiamond - Wang, Jian-Tao; Chen, Changfeng; Mizuseki, Hiroshi (AMER PHYSICAL SOC, 2020)
We report on the finding of a hard carbon structure in body centered cubic (I2(1)3) symmetry that possesses an extremely high bulk modulus (386 GPa) and Vickers hardness (60 GPa) comparable to that of c-BN and diamond. This carbon phase has a 14-atom primitive cell in an all-sp(3) a bonding network comprising five-membered rings, making it a truly full-fledged pentadiamond. Total energy calculations show that it is more stable than the previously reported diamondlike six-membered-ring bonded BC8 and BC12 carbon phases. Electronic band structure calculations show that it is an insulator with an indirect band gap of 5.64 eV. Simulated x-ray diffraction patterns and lattice parameters provide an excellent match to the previously unexplained distinct diffraction peaks found in carbon soot. The present results establish a distinct type of carbon phase and offer insights into its outstanding structural, mechanical, and electronic properties.
Keywords: HIGH-PRESSURE; DIAMOND; CLASSIFICATION; ALLOTROPES; GRAPHENE; HARDNESS